Solidification Kinetics of Zr\(_{50}\)Cu\(_{35}\)Ni\(_{15}\) Alloy: Experiments on the Ground and in Microgravity - Yu, Chu; Wilke, Johannes; Hempel, Hans-Jürgen; Fang, Yindong; Lippmann, Stephanie; Galenko, Peter K. (Proceedings of the 8\(^{th}\) International Conference on Solidification and Gravity, 2025)
Experimental results on solidification kinetics of the glass forming Zr50Cu35Ni15 alloy are presented with measurements conducted under terrestrial and reduced gravity conditions. Alloy samples are processed in an Electromagnetic Levitation Facility (EML) installed on the ground (for measurements in the 1g-gravity) and in AIRBUS during parabolic flight campaigns (providing measurements under a reduced gravity field). The microstructure has been investigated by the Energy-dispersive X-ray (EDX) method with identification of the primary and secondary crystalline patterns. In the evolution analyses of the recalescence fronts, it is found that the square shape of the recalescence front changes from a square shape to a hexagonal shape as the undercooling increases from low to intermediate values. This change in the shape of the recalescence front might be attributed to the kinetic transition in the preferable crystal growth direction from the \(\langle100\rangle\)- to \(\langle111\rangle\)-direction in the growth of main stems of dendrites. The smooth rounded shape of the recalescence front is detected and attributed to globular transition in the dendrite morphology existing at the highest undercoolings. The microgravity environment enabled reduced convection, allowing clearer insights into solidification kinetics and dendritic behavior. These findings enhance the understanding of solidification processes and have implications for designing advanced glass-forming and intermetallic alloys for practical applications.